Safety and efficacy of topical nitroglycerin ointment on the venous catheterization inpatients referred to emergency ward of Baghiyatollah hospital - M Shaban; Kh Azimi; P Kamali; S Asgarian aminabadi (Tehran University of Medical Sciences, 2002)
This is a double - blind clinical trial to evaluate the safety and efficacy of topical nitroglycerin ointment on venous catheterization in patients referred to emergency ward of Baghiyatollah hospital in 1997.The units under investigation consisting of 70 patients, 40 women and 30 men ranging in age from 20 to 69.The samples were randomly assigned into two equal groups, 35 patients in case group and 35 patients in experimental group. The experimental group received 2% nitroglycerin ointment and the case group received the placebo ointment that was applied prior to venus catheterization on the skin of the dorsum of the hand, wrist or front part of forearm.To collect data, an observational checklist was used in which demographic characteristics, and efficacy and immunity of the ointment were recorded.The findings revealed that the vein diameter in case group was not increased after applying the ointment, while it was considerably increased in experimental group from 4 mm to 6.6 mm. Although the method of catheterization in two groups was the same, catheterization in case group was more difficult than experimental group. Using T.test, the findings revealed that there was statistically significant relationship between vein diameter before and after applying the ointment in experimental group and after applying it in case and experimental groups (PO.001). Moreover, tachycardia and hypotension was not observed in both groups during 15, 30, 45 minutes and one and two hours immediately after applying the ointment, however in both groups, a sort of mild headache was observed. The findings also showed that there was significant relationship in observing the vein after catheterization in two groups (P<0.2). However, before applying the ointment, there was significant relationship in observing the vein in the experimental group. Furthermore, after applying the ointment, arhythmia appeared, but it was not significant.The results showed that applying nitroglycerin ointment was a useful method in expanding the peripheral veins, therefore, it resulted in easy venous catheterization.